Investigation of Anticonvulsant activity of Phyllanthus urinaria L. in Swiss albino rats (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Phyllanthus urinaria commonly known as Bhumyamlaki is an annual perennial plant indigenous to the Indian subcontinent and is used in traditional medicine as antidiabetic, antihypertensive, anti-inflammatory, antimalarial, and hepatoprotective. An ayurvedic text such as Bhavprakashnighantu describes P. urinaria is useful in reducing hyperactivity and beneficial in the treatment “Pittajapasmara” (type of epilepsy as described in ayurveda). The present study aimed to evaluate traditional claims in the folk medicine of bhumyamlaki (P. urinaria) which can be beneficial in the treatment of epilepsy using wistar albino rats. The anticonvulsant activity was carried out using the MES-induced seizure and PTZ-induced seizure model. In the MES-induced seizure model, animals were divided into a group of 5 (n=6). Group I was treated with saline, group II-IV was treated with ethanolic extract of P. urinaria (EPU) at the dose level of 100, 200 and 400 mg/kg. Standard drug phenytoin (25 mg/kg., p.o) was given to group V. Similar grouping was done in PTZ induced seizure model with deviation of the standard group which was treated with diazepam (4 mg/kg., i.p). Anticonvulsant activity was noted by accessing the parameters such as delay in the tonic hind limb extension, stupor, and decrease in mortality. It was observed that ethanolic extract of the whole plant of P. urinaria has significant (p < 0.001) anticonvulsant activity causing the delay in onset of tonic and clonic seizures and improved percentage protection against mortality. Further research is required to find out the exact mechanism of action.